Jenis Jaringan Informasi Dalam Kerjasama Jaringan Antar Perpustakaan - Yusniah Yusniah; Eila Setia Ningsih; Febrian Elly Sakinah Sari (Intitut Agama Islam Nasional Laa Roiba Bogor, 2023)
This article reviews the types of information networks related to library cooperation. Contains several reasons why libraries need to form cooperative networks and the role of information networks. The writing of this article aims to describe why libraries need to collaborate on information networks, what components do libraries need for information networks, the forms of information networks and information networks that are already available in Indonesia, in this case the author uses study methods obtained from various trusted sources. the results of the study that can be obtained from reliable sources, the authors conclude as a source of information and distributors who desperately need information, in this case a source of information to solve problems that cannot be solved alone and to maximize the use of the library. an example of two libraries working together to create a master catalog aimed at maximizing the use of library materials. In collaboration between libraries what is needed is an information network, collaboration between libraries and information networks to support all activities that occur in the library. The library network can be implemented from computer networks, namely bus-type networks, ring type networks, star type networks, tree type networks. Meanwhile, information networks include guided networks, non-guided networks, guided networks with special centers and non-guided networks with special centers. Keywords: information networks , library cooperation